The Mechanism of Auriculotherapy: A Case Report Based on the Fractal Structure of Meridian System - Filho, Mario Bernardo; de Sá-Caputo, Danúbia da Cunha; Marin, Pedro J; Chang, Shyang (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Meridian system of acupuncture has been deciphered as the fractal continuum of neurovascular bundles and its smaller branches. Hence, based on the proposed theory, the important sensory organ of ears should be able to exert its influence on visceral organs and peripheral limbs. The aim is to verify possible correlation between the external ear stimulation and the muscle of biceps brachii via electromyograms (EMGs). A region between the points of elbow and shoulder in the scaphoid fossa (upper arm) was chosen. Before the recording of surface EMG signals, each subject was asked to carry out maximum voluntary isometric contractions (MVIC) of the arm. Due to the necessity of having an appropriate control group for this type of study, the same volunteers served as control. Consequently, each subject performed the three treatments of control, sham, and acupressure in random order. EMG signals were recorded. Results indicate that the acupressure with finger of a specific point possibly with a somatopic relation to the biceps brachii muscle can, in a man, modify the response of the EMG associated with the muscle while the response of the acupressure of a sham point has different responses. Moreover, the MVIC parameters were higher in acupressure treatment than control and sham treatments for both subjects. In conclusion, the analysis of the findings reported permits to speculate that the stimulation with the fingers of region between the points of elbow and shoulder in the scaphoid fossa of the ear presents electromyographic response related to the biceps brachii muscle.